Productive zakat distribution in improving mustahik welfare: CIBEST model approach - Sinta Octavia Fabber Karunia; Faizal Amir (Journal of Enterprise and Development (JED), 2024)
Purpose — This research aims to determine the positive impact of the productive zakat program on Mustahik's welfare through increasing income and spiritual well-being and reducing poverty levels.Method — We employed a purposive sampling method in our sampling technique. The criteria for respondents selected as samples in this study were mustahiq, who received zakat from BAZNAS and were Muslim. The data for this research were obtained by distributing questionnaires directly through visits to Mustahiq's homes. The collected data were then processed using the Wilcoxon test and CIBEST model analysis. The Wilcoxon test determined the average difference in income before and after receiving zakat. Meanwhile, the CIBEST model was used to evaluate Mustahik's welfare.Result — The findings of this research show that mustahik recipients of productive zakat assistance can improve their financial conditions and materially enhance their circumstances. Overall, the research results confirm that the BAZNAS effective zakat program has had a positive impact on Mustahik's welfare, by increasing income, spiritual well-being, and reducing poverty levels.Practical implications  — The distribution of productive zakat must continue to be improved, both in terms of the quality of its management and the utilization of abundant zakat funds, to achieve a more optimal positive impact on Mustahik's welfare.